Conserved Subgroups of the Plant-Specific RWP-RK Transcription Factor Family Are Present in Oomycete Pathogens - Yin, Maozhu; Zhang, Zhichao; Xuan, Mingrun; Feng, Hui; Ye, Wenwu; Zheng, Xiaobo; Wang, Yuanchao (Frontiers in Microbiology, 2020)
Nitrogen is a major constituent of proteins, chlorophyll, nucleotides, and hormones, and has profound effects on plant growth and productivity. RWP-RK family transcription factors (TFs) are key regulators that bind to cis-acting elements in the promoter regions of nitrogen use efficiency-related genes and genes responsible for gametogenesis and embryogenesis. The proteins share a conserved RWPxRK motif; have been found in all vascular plants, green algae, and slime molds; and are considered to be a plant-specific TF family. In this study, we show that RWP-RK proteins are also widely present in the Stramenopila kingdom, particularly among the oomycetes, with 12–15 members per species. These proteins form three distinct phylogenetic subgroups, two of which are relatively closely related to the nodule inception (NIN)-like protein (NLP) or the RWP-RK domain protein (RKD) subfamilies of plant RWP-RK proteins. The donor for horizontal gene transfer of RWP-RK domains to slime molds is likely to have been among the Stramenopila, predating the divide between brown algae and oomycetes. The RWP-RK domain has secondary structures that are conserved across plants and oomycetes, but several amino acids that may affect DNA-binding affinity differ. The transcriptional activities of orthologous RWP-RK genes were found to be conserved in oomycetes. Our results demonstrate that RWP-RK family TF genes are present in the oomycetes, and form specific subgroups with functions that are likely conserved. Our results provide new insights for further understanding the evolution and function of this TF family in specific eukaryotic organisms.